Compulsory Arbitration in Nonunion Employee Relations: A Strategic Ethical Analysis - Berman, Debra (Journal of business ethics, 2006)
The purpose of this paper is to provide an overview of the most recent public policy and ethical issues as they relate to the growing usage of nonunion employment arbitration particularly in relation to financial services firms and professional firms. In this era of increasing employment-related litigation, it is wise from an employer’s point of view to find alternative procedures that offer assurances of fairness yet provide expeditious means for resolving disputes. From an employee’s vantage point, however, it is essential that the fundamental issue of procedural and substantive due process be maintained and guaranteed. Therefore, a number of strategic ethical issues arise: How should employment arbitration procedures be designed following the Due Process Protocol of the Task Force on Alternative Dispute Resolution in Employment? How should arbitration procedures follow the national rules for the resolution of employment disputes of the American Arbitration Association? Do recent court decisions shed light on these issues? What ethical principles can be gleaned from these public policy pronouncements? A final objective of this paper is to study some of the current initiatives on this topic.